2016
DOI: 10.4172/2161-119x.1000251
|View full text |Cite
|
Sign up to set email alerts
|

Pilomatrixoma-A Case Report

Abstract: A 27 year old female attended our ENT out patient department with swelling in the left preauricular region. Excision biopsy was done and was reported as pilomatrixoma. Pilomatrixoma is a rare tumor in head and neck region. It is commonly misdiagnosed and often missed while making a differential diagnosis. It is a benign tumour but occasionally it may become malignant. For this reason surgical excision is the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The lesions are oval with welldemarcated margins. Some encapsulated Sannigrahi et al (2016) lesions have also been observed. Moreover, the overlying skin is usually normal, but in some cases, a reddish-bluish hue can be seen due to angiogenesis Birman et al (2009).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The lesions are oval with welldemarcated margins. Some encapsulated Sannigrahi et al (2016) lesions have also been observed. Moreover, the overlying skin is usually normal, but in some cases, a reddish-bluish hue can be seen due to angiogenesis Birman et al (2009).…”
Section: Discussionmentioning
confidence: 94%
“…Both of these signs are typical of pilomatrixoma, thus the most helpful clues for diagnosis Kashif and Shastry (2016). The differential diagnoses of pilomatrixoma include epidermoid cyst, sebaceous cysts, dermoid cysts, hematoma, trichoepithelioma, basal cell epithelioma, unidentified masses, and foreign bodies reactions Sannigrahi et al (2016), Birman et al (2009). Often the lesions of pilomatrixoma are misdiagnosed as one of the differentials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations